PENGARUH KUALITAS PRODUK, HARGA DAN IKLAN TELEVISI TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK MEREK CITRA HAND AND BODY LOTION DI PARIAMAN - Wahyu Erdalina; Susi Evanita (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
The objective of this research is to analyze the influence of product quality, price and promotion to buying decision making of  Citra hand and body lotion in Pariaman. The research surveyed 100 respondents in Pariaman using accidental sampling method. Primary data gained by conducting observation, interview and questioner dissemination (that the validity and reliability of the questioner had already been tested). The data collected analyzed by using logistic regression method. The result of this research shows that product quality, price and promotion in televition are significantly influence toward the buying decision makin  in Pariaman. Key words:  Product Quality, Price, Promotion in television, and Buying Decision Making.